Preparation method and application of hydrogen electrode for alkaline electrolysis of water with cerium-lanthanum non-noble metal coating
Patent Information
- Application Number
- CN202610841279.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-11
- Publication Date
- 2026-09-22
- Estimated Expiration
- 2046-06-11
AI Technical Summary
[0004]然而,现有涂层方案普遍采用单一配方一次镀制,难以同时兼顾电极的耐腐蚀性和催化活性
通过内外层差异化配方设计,内层不含铈镧以提供致密防护,外层铈镧共掺杂以提高催化活性,解决了单涂层难以兼顾耐腐蚀性与析氢性能的问题。
Smart Images

Figure CN122382546B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of water electrolysis for hydrogen production technology, and in particular to a method for preparing and applying an alkaline water electrolysis electrode with a cerium-lanthanum non-precious metal coating. Background Technology
[0002] With the rapid growth in demand for hydrogen production from renewable energy sources, alkaline water electrolysis has become the mainstream route for industrial green hydrogen production due to its advantages such as low cost and long lifespan. However, wind and solar power generation is intermittent and fluctuates, requiring water electrolysis electrodes to have high catalytic activity, excellent dynamic response, and long cycle life under high current density.
[0003] While the Raney nickel electrode commonly used in industry is inexpensive, it has a high hydrogen evolution overpotential, exhibits significant activity decay at high current densities, and suffers severe oxidation and corrosion under frequent start-stop conditions, making it difficult to meet the long-term stable operation requirements of wind-solar combined use scenarios. To improve electrode performance, existing technologies attempt to deposit nickel-cobalt-phosphorus-boron alloy coatings on nickel substrates. Some studies introduce rare earth elements such as cerium and lanthanum to modulate the electronic structure and lower the hydrogen evolution reaction energy barrier.
[0004] However, existing coating methods generally employ a single-formulation, one-time plating process, making it difficult to simultaneously achieve both corrosion resistance and catalytic activity of the electrode. More importantly, in rare earth doping electroless plating, the lack of precise design in the stoichiometric ratio of reducing agent to metal ions results in extremely low actual deposition efficiency of rare earth elements. The cerium and lanthanum content in the coating is far lower than the designed values for the plating solution, significantly reducing the doping effect. Furthermore, the high-temperature sintering treatment used to enhance the adhesion between the coating and the substrate often leads to crystallization brittleness of the amorphous coating above the crystallization temperature, generating microcracks and weakening the coating's protective effect.
[0005] The aforementioned problems make it difficult for existing technologies to achieve a balance between cost, catalytic activity, and long lifespan. There is an urgent need to develop a non-precious metal electrode preparation scheme that is scientifically formulated, has a reasonable process, and takes into account both protection and catalysis. Summary of the Invention
[0006] The main objective of this invention is to provide a method for preparing an alkaline water electrolysis hydrogen production electrode with a cerium-lanthanum non-precious metal coating. Through differentiated formulation design of inner and outer layers, the inner layer provides corrosion resistance and protection, while the outer layer improves hydrogen evolution catalytic activity through cerium-lanthanum rare earth co-doping. At the same time, low-temperature sintering is carried out in the amorphous temperature range to avoid crystallization and cracking of the coating.
[0007] To achieve the above objectives, the present invention provides a method for preparing an alkaline water electrolysis hydrogen production electrode with a cerium-lanthanum non-noble metal coating, comprising the following steps: The Raney nickel mesh substrate is pretreated to remove surface oil and oxide layers; Prepare an inner protective layer reaction solution, wherein the reaction solution contains nickel salt, cobalt salt, hypophosphite, dimethylaminoborane, and a complexing agent, and wherein the inner protective layer reaction solution does not contain cerium salt or lanthanum salt; The Raney nickel mesh substrate is immersed in the inner protective layer reaction solution for a first chemical plating, and after drying, the Raney nickel mesh substrate is sintered under an argon protective atmosphere to form an inner protective layer. Prepare an outer catalyst layer reaction solution, wherein the reaction solution comprises nickel salt, cobalt salt, cerium salt, lanthanum salt, hypophosphite, dimethylaminoborane, and a complexing agent; The Raney nickel mesh substrate with the inner protective layer is immersed in the outer catalytic layer reaction solution for a second chemical plating. After drying, the outer catalytic layer is formed, and the electrode is obtained.
[0008] Furthermore, the step of preparing the inner protective layer reaction solution includes: Add nickel salt, cobalt salt, and complexing agent to deionized water and stir until completely dissolved. Then add hypophosphite and dimethylaminoborane in sequence, stir evenly, and bring to a final volume. The pH value was adjusted to 8.8-9.2 with ammonia water to obtain the inner protective layer reaction solution, in which the molar ratio of nickel salt to cobalt salt was 2:1-3:1, and the molar ratio of hypophosphite to dimethylaminoborane was 0.6:1-1:1.
[0009] Furthermore, the step of immersing the Raney nickel mesh substrate in the inner protective layer reaction solution for a first chemical plating, drying it, and then sintering the Raney nickel mesh substrate under an argon protective atmosphere to form the inner protective layer includes: The Raney nickel mesh substrate is immersed in the inner protective layer reaction solution and reacted at room temperature with magnetic stirring for 2-3 hours. It is then removed, rinsed with pure water, and dried in an oven at 80°C for 1 hour. The dried Raney nickel mesh substrate is placed in a muffle furnace and heated to 340-360°C at a heating rate of 2-3°C / min under an argon protective atmosphere. It is then held at that temperature for 1.5-2.5 hours and allowed to cool naturally to room temperature to form the inner protective layer.
[0010] Furthermore, in the outer catalyst layer reaction solution, the molar ratio of nickel salt to cobalt salt is 2:1-3:1, the molar ratio of cerium salt to lanthanum salt is 1:1, and the total molar amount of cerium salt and lanthanum salt is 5-10% of the total molar amount of nickel salt and cobalt salt.
[0011] Furthermore, the outer catalytic layer has a sheet-like stacked morphology, and the inner protective layer has a dense amorphous structure after sintering.
[0012] Furthermore, the second chemical plating is carried out under stirring conditions at room temperature for 2.5-3.5 hours. After the reaction is completed, the sample is rinsed with pure water and dried at 80°C.
[0013] The present invention also provides an alkaline water electrolysis hydrogen production electrode containing a cerium-lanthanum non-precious metal coating, which is prepared by the preparation method described above.
[0014] Furthermore, in the outer catalyst layer, the total atomic percentage of cerium and lanthanum is 2-5%, and the atomic ratio of phosphorus to boron is 3:1-5:1.
[0015] Furthermore, the inner protective layer is an amorphous alloy layer of nickel-cobalt-phosphorus-boron without cerium and lanthanum, and the outer catalytic layer is an alloy layer of nickel-cobalt-phosphorus-boron containing cerium and lanthanum.
[0016] The present invention also provides an application of an alkaline water electrolysis hydrogen production electrode with a cerium-lanthanum non-precious metal coating as described above, wherein the electrode is used in an alkaline water electrolysis hydrogen production device.
[0017] The method for preparing an alkaline water electrolysis hydrogen production electrode with a cerium-lanthanum non-noble metal coating provided in the above embodiments has the following beneficial effects: By designing differentiated formulations for the inner and outer layers, the inner layer is free of cerium and lanthanum to provide dense protection, while the outer layer is co-doped with cerium and lanthanum to improve catalytic activity, thus solving the problem that single-layer coatings cannot simultaneously achieve both corrosion resistance and hydrogen evolution performance.
[0018] By precisely controlling the electron stoichiometry ratio of the reducing agent and metal ions, the actual deposition efficiency of rare earth elements was significantly improved, making the coating composition more consistent with the design value.
[0019] By employing a low-temperature sintering process that is lower than the crystallization temperature of amorphous alloys, the coating is effectively prevented from crystallizing and cracking while ensuring the adhesion between the coating and the substrate, thus significantly improving the service life of the electrode under fluctuating operating conditions. Attached Figure Description
[0020] Figure 1 This is a flowchart of a method for preparing an alkaline water electrolysis hydrogen production electrode with a cerium-lanthanum non-precious metal coating, as provided in an embodiment of the present invention. Figure 2 This is the overall morphology of the Raney nickel rough surface without coating after cleaning in this invention; Figure 3 This describes the fine morphology of the rough Raney nickel surface without a deposited coating after cleaning, as described in this invention. Figure 4 This describes the overall morphology of the nickel-cobalt-phosphorus-boron alloy catalytic layer stacked structure containing cerium and lanthanum in the outer layer of this invention; Figure 5 This is a fine feature of the nanosheet-like structure of the outer cerium and lanthanum-containing nickel-cobalt-phosphorus-boron alloy catalytic layer in this invention; Figure 6 This describes the dense surface morphology of the inner layer of the nickel-cobalt-phosphorus-boron amorphous alloy layer that does not contain cerium or lanthanum after sintering. Figure 7 This refers to the dense surface morphology of nanoparticles in the inner layer of the nickel-cobalt-phosphorus-boron amorphous alloy layer that does not contain cerium or lanthanum after sintering in this invention. Figure 8 This is a comparison of linear scanning voltammetry curves and hydrogen evolution overpotentials of different electrodes in the electrolyte in this invention; Figure 9 This is a table showing the long-term stability test results of different electrodes under continuous start-up and shutdown conditions in this invention; The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0021] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0022] Reference Figure 1 This is a schematic flowchart of a method for preparing an alkaline water electrolysis hydrogen production electrode with a cerium-lanthanum non-noble metal coating, as proposed in this invention, including the following steps: S1, Pre-treat the Raney nickel mesh substrate to remove surface oil and oxide layer; S2, prepare the inner protective layer reaction solution, the reaction solution contains nickel salt, cobalt salt, hypophosphite, dimethylaminoborane, and complexing agent, the inner protective layer reaction solution does not contain cerium salt and lanthanum salt; S3, the Raney nickel mesh substrate is immersed in the inner protective layer reaction solution for the first chemical plating, and after drying, the Raney nickel mesh substrate is sintered under an argon protective atmosphere to form the inner protective layer. S4, Prepare the outer catalyst layer reaction solution, wherein the reaction solution contains nickel salt, cobalt salt, cerium salt, lanthanum salt, hypophosphite, dimethylaminoborane, and a complexing agent; S5, the Raney nickel mesh substrate with the inner protective layer is immersed in the outer catalytic layer reaction solution for a second chemical plating, and after drying, the outer catalytic layer is formed to obtain the electrode.
[0023] As described in step S1 above, the Raney nickel mesh substrate is ultrasonically cleaned sequentially in pure water, anhydrous ethanol, and acetone for 10 to 20 minutes each. The ultrasonic cleaning process utilizes cavitation to remove surface-adhered processing grease and organic contaminants. After cleaning, the substrate is transferred to a 3 mol / L nitric acid solution and immersed at room temperature for 3 to 5 minutes. The strong oxidizing properties of nitric acid effectively dissolve and remove the loose oxide scale generated during storage and processing of the Raney nickel mesh. Simultaneously, it performs micron-level etching on the nickel mesh surface, forming uniformly distributed micro-pits to expand the effective adhesion area for subsequent plating layers. After nitric acid treatment, the substrate is quickly rinsed with pure water and then immersed in a 1 mol / L sodium hydroxide solution at room temperature for another 3 to 5 minutes. This alkaline treatment neutralizes residual acidic substances and further removes loose but not yet detached oxide particles caused by acid etching. After alkaline immersion, the substrate is repeatedly rinsed with plenty of pure water until the rinsing solution is neutral. The cleaned Raney nickel mesh substrate is then placed in a 60°C oven to dry for 1 hour. Once completely dry, the substrate is removed for later use. The immersion time and temperature of various solutions in the entire pretreatment process were optimized to ensure both surface purification and activation effects while avoiding excessive etching that could weaken the strength of the nickel mesh skeleton. The pretreated Raney nickel mesh substrate has a clean, grayish-white metallic luster, no visible oxide spots, and good hydrophilicity.
[0024] As described in step S2 above, anhydrous nickel nitrate, anhydrous cobalt nitrate, sodium succinate, sodium hypophosphite monohydrate, and citric acid monohydrate are added sequentially to deionized water. The mixture is stirred continuously at room temperature until all solutes are completely dissolved, resulting in a clear green solution. In this step, the molar ratio of nickel to cobalt is controlled within the range of 2:1 to 3:1. A higher nickel content than cobalt is beneficial for improving the coating's resistance to alkaline corrosion, while ensuring the lattice matching between the inner protective layer and the Raney nickel mesh substrate. Sodium hypophosphite monohydrate serves as a phosphorus source and auxiliary reducing agent, and its addition amount is controlled within a molar ratio of 0.6:1 to 1:1 with the main reducing agent, dimethylaminoborane. This ratio can form an alloy structure with a phosphorus-boron atomic ratio of 3:1 to 5:1 in the coating. This structure plays a crucial role in improving the density and thermal stability of the amorphous coating. Sodium succinate and citric acid monohydrate are used in combination as complexing agents. Sodium succinate, as the main complexing agent, effectively complexes nickel and cobalt ions, inhibiting the formation of hydroxide precipitates under alkaline conditions. Citric acid monohydrate, as an auxiliary complexing agent, further stabilizes the plating solution and prevents self-decomposition during prolonged plating. After the inorganic salts and complexing agents are completely dissolved, dimethylaminoborane is added to the solution, and stirring continues until uniformly dispersed. Dimethylaminoborane is the main reducing agent in the electroless plating process; each molecule provides 6 electrons to reduce nickel and cobalt ions to their metallic state. Its reduction potential drives the autocatalytic deposition of nickel-cobalt alloy on the Raney nickel mesh surface under alkaline conditions. After stirring, the solution is brought to a final volume of 200 ml. Ammonia is slowly added dropwise to adjust the pH value to between 8.8 and 9.2, thus obtaining the inner protective layer reaction solution. This reaction solution does not contain any cerium salts or lanthanum salts. The inner layer only serves the functions of corrosion resistance and adhesion. The absence of rare earth elements can avoid the formation of heterogeneous phase boundaries in the coating, ensuring the formation of a uniform and dense amorphous nickel-cobalt-phosphorus-boron alloy layer after sintering.
[0025] As described in step S3 above, the pretreated Raney nickel mesh substrate is completely immersed in the inner protective layer reaction solution prepared in S2, and the reaction is continued for 2.5 hours at room temperature with magnetic stirring at 300 rpm. During the electroless plating process, dimethylaminoborane and sodium hypophosphite monohydrate synergistically release electrons at the catalytic active sites on the nickel mesh surface. Nickel and cobalt ions are reduced to their metallic state and co-deposited on the substrate surface. At the same time, phosphorus and boron are embedded in the interstitial spaces of the nickel-cobalt alloy lattice as interstitial atoms, forming a uniform nickel-cobalt-phosphorus-boron quaternary amorphous coating. Since the reaction solution does not contain cerium or lanthanum salts, the coating composition consists only of four elements: nickel, cobalt, phosphorus, and boron. This avoids the heterogeneous phase boundaries that rare earth elements may introduce in the plating state, which is beneficial for the uniform densification of the coating structure during sintering. After plating, the substrate is removed from the reaction solution and repeatedly rinsed with pure water to remove residual plating solution and loose adhering substances from the surface. Then, it is placed in an 80°C oven to dry for 1 hour. After drying, the samples were transferred to a muffle furnace for sintering. High-purity argon was pre-purged into the muffle furnace to purge air from the furnace chamber before sintering, maintaining an argon protective atmosphere throughout the process to prevent oxidation of the coating during heating. The heating rate was set at 2°C per minute; slow heating effectively released thermal stress caused by the difference in thermal expansion coefficients between the coating and the substrate, preventing microcracks from forming in the coating during sintering. The sintering temperature was set at 350°C, with a holding time of 2 hours. This temperature of 350°C is lower than the crystallization temperature of the nickel-cobalt-phosphorus-boron amorphous alloy. During sintering, the coating maintained its amorphous structure, preventing grain nucleation and growth. Microscopic pores and loose areas in the coated state were eliminated only through short-range atomic diffusion, resulting in a denser overall coating. After holding, the samples cooled naturally to room temperature with the furnace. The resulting nickel-cobalt-phosphorus-boron inner protective layer had a smooth and dense surface and was firmly bonded to the Raney nickel mesh substrate.
[0026] As described in step S4 above, anhydrous nickel nitrate, anhydrous cobalt nitrate, anhydrous cerium nitrate, anhydrous lanthanum nitrate, sodium succinate, sodium hypophosphite monohydrate, and citric acid monohydrate are added sequentially to deionized water and stirred continuously at room temperature until completely dissolved. The molar ratio of nickel to cobalt is maintained within the range of 2:1 to 3:1 to ensure a smooth transition in composition gradient between the outer catalytic layer and the inner protective layer, avoiding weak adhesion zones at the interface due to abrupt changes in composition. The introduction of cerium and lanthanum salts is a core feature distinguishing the outer catalytic layer from the inner protective layer. The molar ratio of cerium nitrate to lanthanum nitrate is set at 1:1, and the total molar amount of the two rare earth ions is controlled to be 5% to 10% of the total molar amount of nickel and cobalt. Setting the rare earth doping amount within this range allows for the formation of uniformly dispersed cerium and lanthanum active sites in the coating. By regulating the electronic state density near the Fermi level of the nickel-cobalt alloy through the 4f electrons of the lanthanides, the adsorption energy barrier of intermediate hydrogen atoms in the hydrogen evolution reaction is reduced, while avoiding excessive doping that could lead to the precipitation of rare earth hydroxides in the alkaline plating solution. The amounts of sodium succinate and citric acid monohydrate in the complexing agent system are consistent with those in the inner layer reaction solution to ensure good stability of the plating bath after the introduction of trivalent rare earth ions. After all inorganic salts and complexing agents have dissolved, dimethylaminoborane is added to the solution, stirred evenly, and then brought to a final volume of 200 mL. The pH value is adjusted to 9.0 ± 0.2 with ammonia. The total electron supply of the reducing agent is maintained at 1.1 to 1.2 times the total electron requirement of the metal ions to ensure that cerium and lanthanum ions are effectively reduced and embedded in the alloy coating under the synergistic effect of nickel-cobalt deposition.
[0027] As described in step S5 above, after the substrate carrying the inner protective layer is immersed in the reaction solution, the original nickel-cobalt-phosphorus-boron amorphous alloy layer on its surface acts as a catalytically active surface, initiating an oxidation reaction between dimethylaminoborane and sodium hypophosphite monohydrate. The released electrons simultaneously reduce nickel ions, cobalt ions, cerium ions, and lanthanum ions in the plating solution and deposit them on the inner protective layer. During the deposition process, cerium and lanthanum atoms enter the nickel-cobalt alloy lattice in the form of substitutional solid solution or interstitial solid solution, while phosphorus and boron atoms fill the interstitial positions of the lattice. The five elements together form a rare earth-doped nickel-cobalt-phosphorus-boron pentagonal amorphous alloy layer. Unlike the dense and smooth morphology of the inner layer, the outer catalytic layer spontaneously forms a large number of interwoven sheet-like structures during the chemical plating process. The nanoscale flakes are stacked and arranged in different orientations, significantly increasing the actual surface area of the electrode and exposing more hydrogen evolution reaction active centers. After the plating is completed, the electrode is removed from the reaction solution and repeatedly rinsed with pure water to remove residual alkaline plating solution and loose adhering substances on the surface. Then, it is placed in an 80°C oven to dry for 1 hour. After the outer catalytic layer is deposited, it is not sintered again to preserve its high specific surface area, sheet-like stacked morphology, and amorphous structure. The electrode after drying is a double-coated alkaline water electrolysis hydrogen production electrode with an inner protective layer and an outer catalytic layer. The inner layer provides corrosion resistance and substrate adhesion, while the outer layer provides high hydrogen evolution catalytic activity through cerium-lanthanum rare earth co-doping. The two layers transition naturally in composition gradient and there is no obvious heterogeneous interface. It exhibits excellent stability under industrial high current density and frequent start-stop conditions.
[0028] The present invention will be specifically described below through examples.
[0029] Example 1 By molar amount, 200 mL of the inner protective layer reaction solution contains: 0.42 mol of nickel, 0.18 mol of cobalt, 0.19 mol of dimethylaminoborane, 0.15 mol of sodium hypophosphite monohydrate, 0.3 mol of sodium succinate, and 0.02 mol of citric acid monohydrate. The total number of electrons required by the metal ions is 1.2 mol, which is the sum of the divalent nickel and cobalt ions. The total number of electrons provided by the reducing agent is 1.44 mol, which is the sum of 1.14 mol provided by dimethylaminoborane and 0.3 mol provided by sodium hypophosphite monohydrate. The excess ratio of the reducing agent is about 20%, which is slightly higher than that of the outer layer to ensure a denser inner layer coating.
[0030] The 200 mL outer catalyst layer reaction solution contains: 0.4 mol nickel, 0.2 mol cobalt, 0.035 mol cerium, 0.035 mol lanthanum, 0.21 mol dimethylaminoborane, 0.14 mol sodium hypophosphite monohydrate, 0.3 mol sodium succinate, and 0.02 mol citric acid monohydrate. The total electron requirement of the metal ions is 1.41 mol, which is the sum of divalent nickel and cobalt ions and trivalent cerium and lanthanum ions. The total electron supply of the reducing agent is 1.54 mol, which is the sum of 1.26 mol provided by dimethylaminoborane and 0.28 mol provided by sodium hypophosphite monohydrate. The excess ratio of the reducing agent is approximately 9.2%, which is within the optimal range of 1.1-1.2 times.
[0031] The preparation steps are as follows: The Raney nickel mesh substrate was ultrasonically cleaned for 15 minutes each with pure water, ethanol, and acetone, then soaked in 3M nitric acid solution at room temperature for 5 minutes, followed by soaking in 1M sodium hydroxide solution at room temperature for 5 minutes. After rinsing with pure water, it was dried in an oven at 60°C for 1 hour for later use.
[0032] To prepare the inner protective layer reaction solution, add 76.73 g of anhydrous nickel nitrate, 32.93 g of anhydrous cobalt nitrate, 0.3 mol of sodium succinate, 15.90 g of sodium hypophosphite monohydrate, and 0.02 mol of citric acid monohydrate to deionized water. Stir until completely dissolved, then add 11.19 g of dimethylaminoborane. After stirring evenly, bring the volume to 200 mL and adjust the pH to 9.0 ± 0.2 with ammonia. Immerse the pretreated Raney nickel mesh substrate in the inner protective layer reaction solution and react at room temperature with magnetic stirring at 300 rpm for 2.5 hours. Remove, rinse with pure water, and dry in an oven at 80°C for 1 hour.
[0033] The dried sample was placed in a muffle furnace for sintering. Under an argon protective atmosphere, the temperature was increased to 345°C at a rate of 2.5°C per minute, and sintered at that temperature for 2 hours. The sample was then allowed to cool naturally to room temperature. After sintering, the inner protective layer exhibited a dense amorphous structure with a smooth surface free of microcracks and was firmly bonded to the substrate.
[0034] Add 73.08 g of anhydrous nickel nitrate, 36.59 g of anhydrous cobalt nitrate, 11.41 g of anhydrous cerium nitrate, 11.38 g of anhydrous lanthanum nitrate, 0.3 mol of sodium succinate, 14.84 g of sodium hypophosphite monohydrate, and 0.02 mol of citric acid monohydrate to deionized water and stir until completely dissolved. Add 12.37 g of dimethylaminoborane and stir until homogeneous. Adjust the volume to 200 mL and adjust the pH to 9.0 ± 0.2 with ammonia. Immerse the sintered substrate with the inner protective layer into the outer catalyst layer reaction solution and react for 3 hours at room temperature with magnetic stirring at 300 rpm. Remove, rinse with pure water, and dry in an oven at 80 °C for 1 hour to obtain a double-coated alkaline water electrolysis hydrogen production electrode.
[0035] The inner protective layer of the electrode prepared in this embodiment retains its amorphous characteristics after sintering at 345℃, and no obvious crystallization peaks appear in the X-ray diffraction pattern. The outer catalyst layer exhibits a large number of plate-like catalyst stacks on its surface, with a significantly increased specific surface area. At a current density of 10 mA / cm², the overpotential is 47 mV, a decrease of approximately 81% compared to 251 mV on the Raney nickel substrate; at 100 mA / cm², the overpotential is 130 mV, a decrease of approximately 64% compared to 359 mV on the Raney nickel substrate. Under a high current density of 4000 A / m², with three daily cycle starts and stops for 2.5 months, the voltage increased from 2.08 V to 2.16 V, an increase of 0.08 V.
[0036] Example 2 This embodiment prepares a double-coated alkaline water electrolysis hydrogen production electrode with an inner protective layer and an outer catalytic layer.
[0037] The inner protective layer reaction solution, by molar amount, contains the following in 200 mL: 0.45 mol nickel, 0.15 mol cobalt, 0.18 mol dimethylaminoborane, 0.18 mol sodium hypophosphite monohydrate, 0.3 mol sodium succinate, and 0.02 mol citric acid monohydrate. The total number of electrons required by the metal ions is 1.2 mol, which is the sum of the divalent nickel and cobalt ions. The total number of electrons provided by the reducing agent is 1.44 mol, which is the sum of 1.08 mol provided by dimethylaminoborane and 0.36 mol provided by sodium hypophosphite monohydrate. The reducing agent is in excess at 20%, slightly higher than the outer layer, to ensure a denser inner coating.
[0038] The outer catalyst layer reaction solution, by molar amount, contains the following in 200 mL: 0.4 mol nickel, 0.2 mol cobalt, 0.04 mol cerium, 0.04 mol lanthanum, 0.22 mol dimethylaminoborane, 0.14 mol sodium hypophosphite monohydrate, 0.3 mol sodium succinate, and 0.02 mol citric acid monohydrate. The total electron requirement of the metal ions is 1.44 mol, which is the sum of divalent nickel and cobalt ions and trivalent cerium and lanthanum ions. The total electron supply of the reducing agent is 1.6 mol, which is the sum of 1.32 mol provided by dimethylaminoborane and 0.28 mol provided by sodium hypophosphite monohydrate. The excess ratio of the reducing agent is approximately 11.1%.
[0039] The preparation steps are as follows: The Raney nickel mesh substrate was ultrasonically cleaned for 15 minutes each with pure water, ethanol, and acetone, then soaked in 3M nitric acid solution at room temperature for 5 minutes, then soaked in 1M sodium hydroxide solution at room temperature for 5 minutes, rinsed with pure water, and then dried in an oven at 60°C for 1 hour for later use.
[0040] To prepare the inner protective layer reaction solution, add 82.22 g of anhydrous nickel nitrate, 27.44 g of anhydrous cobalt nitrate, 0.3 mol of sodium succinate, 19.08 g of sodium hypophosphite monohydrate, and 0.02 mol of citric acid monohydrate to deionized water and stir until completely dissolved. Add 10.61 g of dimethylaminoborane and stir until homogeneous. Then, bring the volume to 200 mL and adjust the pH to 9.0 ± 0.2 with ammonia. Immerse the pretreated Raney nickel mesh substrate in the inner protective layer reaction solution and react for 2.5 hours at room temperature with magnetic stirring at 300 rpm. Remove the substrate, rinse with pure water, and dry in an oven at 80°C for 1 hour.
[0041] The dried sample was placed in a muffle furnace for sintering. Under an argon protective atmosphere, the temperature was increased to 350°C at a rate of 2°C per minute, and sintered at that temperature for 2 hours, followed by natural cooling to room temperature. After sintering, the inner protective layer exhibited a dense amorphous structure with a smooth surface free of microcracks, and it bonded firmly to the substrate.
[0042] Add 73.08 g of anhydrous nickel nitrate, 36.59 g of anhydrous cobalt nitrate, 13.05 g of anhydrous cerium nitrate, 13.00 g of anhydrous lanthanum nitrate, 0.3 mol of sodium succinate, 14.84 g of sodium hypophosphite monohydrate, and 0.02 mol of citric acid monohydrate to deionized water and stir until completely dissolved. Add 12.96 g of dimethylaminoborane and stir until homogeneous. Make up the volume to 200 mL and adjust the pH to 9.0 ± 0.2 with ammonia. Immerse the sintered substrate with the inner protective layer into the outer catalytic layer reaction solution and react for 3 hours at room temperature with magnetic stirring at 300 rpm. Remove and rinse with pure water, then dry in an oven at 80 °C for 1 hour to obtain a double-coated alkaline water electrolysis hydrogen production electrode.
[0043] The inner protective layer of the electrode prepared in this embodiment retains its amorphous characteristics after sintering at 350℃, and no obvious crystallization peaks appear in the X-ray diffraction pattern. The outer catalyst layer exhibits a large number of lamellar stacked structures, with a significantly increased specific surface area. At a current density of 10 mA / cm², the overpotential is 46 mV, which is about 82% lower than the 251 mV of the Raney nickel substrate; at 100 mA / cm², the overpotential is 124 mV, which is about 65% lower than the 359 mV of the Raney nickel substrate. Under a high current density of 4000 A / m², with three daily cycle starts and stops for 2.5 months, the voltage increased from 2.02 V to 2.11 V, an increase of 0.09 V, demonstrating excellent dynamic response and long service life. EDS analysis of the outer catalyst layer shows that the total atomic percentage of cerium and lanthanum is 4.1%, and the phosphorus-boron atomic ratio is about 5.2:1, which is close to the design value, proving that the stoichiometric optimization significantly improves the rare earth doping efficiency.
[0044] In summary, this invention addresses the technical bottleneck of existing alkaline water electrolysis hydrogen production electrodes in wind and solar co-processing scenarios, which struggle to balance cost, catalytic activity, and long lifespan. It proposes a dual-coating electrode with a cerium-lanthanum non-precious metal coating and its electroless plating preparation method. The electrode uses a Raney nickel mesh as a substrate, constructing a functionally differentiated inner protective layer and an outer catalytic layer through two separate electroless plating processes. The inner layer, free of cerium and lanthanum, forms a dense, amorphous nickel-cobalt-phosphorus-boron alloy layer after argon-protected sintering at 350°C. The outer layer incorporates cerium-lanthanum rare-earth co-doping, which self-catalytically deposits at room temperature to form a pentagonal nickel-cobalt-phosphorus-boron alloy catalytic layer with a sheet-like stacked morphology. In terms of formulation design, by matching the electron stoichiometry between the two reducing agents, dimethylaminoborane and sodium hypophosphite monohydrate, and the metal ions, the excess ratio of the reducing agent is controlled within the range of 1.1 to 1.2 times, effectively solving the technical problem of low cerium-lanthanum deposition efficiency in traditional rare-earth-doped electroless plating. In terms of process design, the sintering temperature is set below the crystallization temperature of the amorphous alloy, avoiding crystallization embrittlement and microcracks caused by high-temperature treatment. The electrode is made entirely of non-precious metal raw materials, and the preparation process is simple and controllable. The double-coating structure maintains high catalytic activity while further improving long-term stability, making it particularly suitable for alkaline water electrolysis hydrogen production systems used in conjunction with intermittent wind and solar power generation.
[0045] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, apparatus, article, or method that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, apparatus, article, or method. Unless otherwise specified, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, apparatus, article, or method that includes that element.
[0046] The above description is only a preferred embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural or procedural transformations made based on the content of the present invention specification and drawings, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.
Claims
1. A method for preparing an alkaline water electrolysis hydrogen production electrode with a cerium-lanthanum non-noble metal coating, characterized in that, Includes the following steps: The Raney nickel mesh substrate is pretreated to remove surface oil and oxide layers; Preparation of the inner protective layer reaction solution: Add anhydrous nickel nitrate, anhydrous cobalt nitrate, sodium succinate, sodium hypophosphite monohydrate, and citric acid monohydrate to deionized water, stir until completely dissolved, add dimethylaminoborane, stir evenly, and bring to a final volume; adjust the pH value to 8.8-9.2 with ammonia water to obtain the inner protective layer reaction solution, wherein the molar ratio of nickel salt to cobalt salt is 2:1-3:1, and the molar ratio of hypophosphite to dimethylaminoborane is 0.6:1-1:1; The Raney nickel mesh substrate is immersed in the inner protective layer reaction solution and subjected to a first chemical plating at room temperature with magnetic stirring for 2-3 hours. After rinsing with pure water, it is dried in an oven at 80°C for 1 hour. The dried Raney nickel mesh substrate is then placed in a muffle furnace and heated to 340-350°C at a heating rate of 2-3°C / min under an argon protective atmosphere. The temperature is held for sintering for 1.5-2.5 hours and then allowed to cool naturally to room temperature to form the inner protective layer, which has a dense amorphous structure. An outer catalyst layer reaction solution is prepared, comprising anhydrous nickel nitrate, anhydrous cobalt nitrate, anhydrous cerium nitrate, anhydrous lanthanum nitrate, sodium hypophosphite monohydrate, dimethylaminoborane, sodium succinate, and citric acid monohydrate. In the outer catalyst layer reaction solution, the molar ratio of nickel salt to cobalt salt is 2:1-3:1, the molar ratio of cerium salt to lanthanum salt is 1:1, and the total molar amount of cerium salt and lanthanum salt is 5-10% of the total molar amount of nickel salt and cobalt salt. The Raney nickel mesh substrate with the inner protective layer is immersed in the reaction solution of the outer catalyst layer for a second chemical plating. After drying, the outer catalyst layer is formed, and the electrode is obtained. The outer catalyst layer has a sheet-like stacked morphology. The inner protective layer is an amorphous alloy layer of nickel-cobalt-phosphorus-boron without cerium and lanthanum, and the outer catalytic layer is an alloy layer of nickel-cobalt-phosphorus-boron containing cerium and lanthanum.
2. The method for preparing the alkaline water electrolysis hydrogen production electrode with a cerium-lanthanum non-noble metal coating according to claim 1, characterized in that, The second chemical plating was carried out under stirring at room temperature for 2.5-3.5 hours. After the reaction was completed, the sample was rinsed with pure water and dried at 80°C.
3. A cerium-lanthanum non-precious metal coated alkaline water electrolysis hydrogen production electrode, characterized in that, It is prepared by the preparation method according to any one of claims 1-2.
4. The alkaline water electrolysis hydrogen production electrode with a cerium-lanthanum non-precious metal coating according to claim 3, characterized in that, In the outer catalyst layer, the total atomic percentage of cerium and lanthanum is 2-5%, and the atomic ratio of phosphorus to boron is 3:1-5:
1.
5. The application of the cerium-lanthanum non-precious metal coated alkaline water electrolysis hydrogen production electrode as described in any one of claims 3-4, characterized in that, The electrode is used in an alkaline water electrolysis hydrogen production device.
Citation Information
Patent Citations
Amorphous reconstructed hydrogen evolution catalyst and preparation method and application thereof
CN121674995A
Ce-doped CoP / NiCoP-coated NM self-supporting structure electrode and preparation method and application thereof
CN121826773A